Sex differences in binge‐like EtOH drinking, corticotropin‐releasing hormone and corticosterone: effects of β‐endorphin. (8th February 2018) - Nentwig, Todd B.; Wilson, Diane E.; Rhinehart, Erin M.; Grisel, Judith E.
Abstract: Binge drinking is an increasingly common pattern of risky use associated with numerous health problems, including alcohol use disorders. Because low basal plasma levels of β‐endorphin (β‐E) and an increased β‐E response to alcohol are evident in genetically at‐risk human populations, this peptide is thought to contribute to the susceptibility for disordered drinking. Animal models suggest that the effect of β‐E on consumption may be sex‐dependent. Here, we studied binge‐like EtOH consumption in transgenic mice possessing varying levels of β‐E: wild‐type controls with 100% of the peptide (β‐E +/+), heterozygous mice constitutively modified to possess 50% of wild‐type levels (β‐E +/−) and mice entirely lacking the capacity to synthesize β‐E (−/−). These three genotypes and both sexes were evaluated in a 4‐day, two‐bottle choice, drinking in the dark paradigm with limited access to 20% EtOH. β‐E deficiency determined sexually divergent patterns of drinking in that β‐E −/− female mice drank more than their wild‐type counterparts, an effect not observed in male mice. β‐E −/− female mice also displayed elevated basal anxiety, plasma corticosterone and corticotropin‐releasing hormone mRNA in the extended amygdala, and all of these were normalized by EtOH self‐administration. These data suggest that a heightened risk for excessive EtOH consumption in female mice is related to the drug's ability to ameliorate an overactive anxiety/stress‐like state. Taken together, our study highlights a critical impact of sex on neuropeptide regulation of EtOH consumption. Abstract : Sensitivity to alcohol's stress relieving effects plays a critical role in susceptibility toward excessive drinking and alcohol use disorders. b‐endorphin deficiency results in sex‐specific alterations in brain stress systems, and enhanced alcohol consumption in female, but not male, mice. Females with low b‐endorphin may represent a population with increased risk for drinking. Overall, our study suggests that b‐endorphin acts to buffer brain stress systems and may safeguard against excessive drinking driven by alcohol's negative reinforcing properties.